A Comparative Analysis of Board Information Disclosures between Deposit Money Banks in Nigeria and Ghana - Oluwagbade, Oluyinka; Dada, Samuel; Adebıyı, Ifeoluwa; Osatuyı, Ogunyemi; Akpan, James (International Journal of Economics and Financial Issues, 2024)
This study compared board information disclosures of 19 Nigerian and Ghanaian deposit money banks, focusing on board meeting attendance records, performance, demographics, education, roles, ethics, anticorruption, code of conduct, policy, and shareholding disclosure, highlighting the importance of transparency for trust and informed decision-making.The sample size was 19 banks, comprising 12 banks from Nigeria and 7 banks from Ghana, and the analysis included independent t-tests and Mann-Whitney U tests. The study compared board disclosure of listed deposit money banks in Nigeria and Ghana. It found that Ghanaian banks disclosed more board demographic information, while Nigerian banks disclosed more board education and training processes. However, there was no significant difference in the disclosures of board roles, functions, chairman’s roles, CEO’s roles, board members’ age, appointment dates, board change, performance, ethics, anti-corruption, code of conduct, policy, and board shareholding between the two countries. The study reveals that listed deposit banks on the Nigerian exchange group disclose similar information to their counterparts on the Ghanaian stock exchange, except for certain aspects like board demographics and board education and training processes. Nigerian and Ghanaian banks should improve disclosure of board change/re-election information, board ethics, anti-corruption, code of conduct, policy, and board members’ age.